NS-Siedlungen in Wien Projekte - Realisierungen - Ideologietransfer - Weinberger, Ingeburg (LIT Verlag GmbH & Co. KG, 2015)
This study investigates the impact of National Socialist ideology and housing settlement projects in Greater Vienna following the Anschluss of Austria to the German Reich in 1938. In this regard, both planned and realized building projects are instructive. The research focused on archival documents of the city of Vienna and contemporaneous primary sources.